PERBEDAAN VARIASI INTENSITAS CAHAYA LAMPU UV TERHADAP JUMLAH LALAT YANG MATI PADA LIGHT TRAP ELECTROCUTOR DI TEMPAT PENGELOLAAN MAKANAN PT. X - Khairun Nisa; Sri Slamet Mulyati; Bambang Purnama, Lubis (Poltekkes Kemenkes Bengkulu, 2024)
Canteen is a place that provides food and beverages to be consumed by many people. According to the Regulation of the Minister of Health No. 5 of 2017 concerning Environmental Health Quality Standards and Health Requirements for Vectors and Disease-Carrying Disturbing Animals and Their Control, the fly quality standard must be less than 2 fly population indexes. Based on the results of preliminary measurements of fly density in the Kitchen of PT. X obtained a fly density index of 8 tails / flygrill, this is not qualified. The purpose of this study was to determine the effect of variations in UV lamp light intensity on dead flies in UV light trap electrocutors. This type of research is experimental research with Postest With Control research design. The treatment given is 3 treatments, namely variations in the light intensity of UV lamps 100 lux, 315 lux and 450 lux. The population in this study was flies in PT.X. samples in this study were flies in the kitchen of PT. X.The results of the study after analysis using the Anova test showed that the P value was 0.000 < α (0.05) which means that there is a significant influence between variations in the intensity of UV lamp light on fly mortality. The results of measuring the calculation of flies trapped with 6 repetitions for 1 hour each variation found as many as 74 flies that died, namely 4 flies in the control, 8 flies at an intensity of 100 lux, 24 flies at an intensity of 315 lux and 38 heads at an intensity of 450 heads. Based on the measurement results on the UV light trap electrocutor tool , the most dead flies are at an intensity of 450 lux.